2000
DOI: 10.1097/00007890-200008270-00014
|View full text |Cite
|
Sign up to set email alerts
|

Intragraft Expression of Transforming Growth Factor-Beta 1 by a Novel Quantitative Reverse Transcription Polymerase Chain Reaction Elisa in Long Lasting Kidney Recipients1

Abstract: This study showed that those patients with elevated CAN scores and higher proteinuria levels had higher TGF-beta1 intragraft expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…A second level of injury occurring after 12 months is associated with arteriolar hyalinosis, ischemic glomerulosclerosis, and secondary fibrosis, which is predominantly due to CNI toxicity (1,2). At the molecular level, there is increasing identification of chemokine, growth factor, and cytokine impact on tubulointerstitial damage (21)(22)(23). Other pathways include cellular senescence, epithelial-to-mesenchymal tubular cell transition, cytokine excess, and structural damage with loss of tubules leading to the formation of atubular glomeruli (24).…”
Section: Discussionmentioning
confidence: 99%
“…A second level of injury occurring after 12 months is associated with arteriolar hyalinosis, ischemic glomerulosclerosis, and secondary fibrosis, which is predominantly due to CNI toxicity (1,2). At the molecular level, there is increasing identification of chemokine, growth factor, and cytokine impact on tubulointerstitial damage (21)(22)(23). Other pathways include cellular senescence, epithelial-to-mesenchymal tubular cell transition, cytokine excess, and structural damage with loss of tubules leading to the formation of atubular glomeruli (24).…”
Section: Discussionmentioning
confidence: 99%
“…Blood group genotypes are usually determined by electrophoresis of the amplicons in agarose gels. The main -TGT TCA ACA CCT ACT ATG CT Exon 5 125 Biotin-AAT ATG GAA AGC ACC TCA TG Exon 9 126 Biotin-AAG ACC TGT ACG CCA ACA CA b-Actin C/c 171 Biotin-(T) 12 TTC AGG GTG CCC TTT GTC ACT T Intron 2 (C) 170…”
Section: Discussionmentioning
confidence: 99%
“…Biotin-TCT ACG TGT TCG CAG CCT AT RHD/RHCE exon 4 K/k 180 Biotin-(T) 12 CGC ATC TCT GGT AAA T Exon 6 126…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, cross sectional studies of renal tissue in patients with established CAN have suggested that the development of glomerulosclerosis and interstitial fibrosis is mediated by the enhanced expression of the profibrotic growth factor, transforming growth factor-β (TGF-β) (13)(14)(15)(16)(17). Primary regulation of TGF-β activity is controlled by cleavage of the latent TGF-β precursor.…”
Section: Introductionmentioning
confidence: 99%